RAINWATER HARVESTING IN KOTA SAMARAHAN - Nasser, R.Afshar; Efarina, A.Hamit (IJRET, 2015)
Water is vital to all forms of life on the Earth, from plants through to animals and humankind. Lack of access to fresh drinking water is one of the major and important constraints to health and development in many countries. Rainwater harvesting refers to the collection and storage of rain. It is still popular in places with limited water resources. Recent drought in a rainy climate throughout the world remind how quickly other countries can run short of water. Since Malaysia has high rainfall intensity, it does not means that Malaysian should not worry about scarcity of water supply. Even the annual rainfall is high and sufficient enough to be consumed, most of the rainwater tend to flow away. The environmental issue such as flooding, global warming and pollution are getting serious day by day due to a rapid development processes in Malaysia. To pursue the need for a more sustainable development, it is possible to implement rainwater harvesting which has been recognized as one of the innovative solutions as an alternative water supply for non-, portable purposes. Designing water harvesting systems into new construction allows the homeowner to be more elaborate and thorough in developing a system. In the case of very simple systems, the payback period may be almost immediate. The objective of this study is to estimate the potential of rainfall to be stored for domestic use and design the rainwater harvesting system using gravitational force suitable for the selected house in Kota Samarahan area. It has been shown that the rainwater harvesting system can support the water demand of the selected house throughout a year even during the dry season. The cost of installation and yearly maintenance for proposed rainwater harvesting is lowered by 59.16 percent as compared with similar rainwater system which is installed on the ground level.